The patient undergoing implant therapy. Summary and consensus statements. The 4th EAO Consensus Conference 2015. Issue 11 (September 2015) - Klinge, Björn; Flemming, Thomas; Cosyn, Jan; De Bruyn, Hugo; Eisner, Barbara M.; Hultin, Margareta; Isidor, Flemming; Lang, Niklaus P.; Lund, Bodil; Meyle, Jürg; Mombelli, Andrea; Navarro, Jose Manuel; et al.
Abstract: Introduction: The assignment for this working group was to update the existing knowledge regarding factors considered being of special relevance for the patient undergoing implant therapy. This included areas where conflicting opinions exists since long or recently has been expressed, like the role of antibiotic prophylaxis in dental implant surgery and peri‐implantitis. Also areas with growing interest and concern such as patient‐reported outcome measures (PROMs) and health‐economy was included in this review. Materials and methods: The literature in the respective areas of interest (antibiotic prophylaxis, peri‐implantitis, patient‐reported outcome measurements and health‐economic aspects) was searched using different strategies for the different papers. Search strategies ranged from a complex systematic review to systematic‐ and narrative reviews, depending on subject and available literature. All collected material was critically reviewed. Four manuscripts were subsequently presented for group analysis and discussion and plenum discussions and concensus approval. The selected areas were considered to be of key importance and relevance for the patient undergoing implant therapy. Results: The results and conclusions of the review process are presented in the respective papers. The group′s conclusions, identified knowledge gaps, directions for future research and concensus statements are presented in this article. The following reviews were available for group discussions and the foundation for subsequent plenary sessions: Lund B, Hultin M, Tranaeus S, Naimi‐Akbar A, Klinge B. (2015) Perioperative antibiotics in conjunction with dental implant placement. A complex systematic review. Renvert S & Quirynen M. (2015) Risk indicators for peri‐implantitis. A narrative review. De Bruyn H, Raes S, Matthys C, Cosyn J. (2015) The current use of patient centered/reported outcomes in implant dentistry. A systematic review. Beikler T & Flemmig T.F. (2015) Economic evaluation of implant‐supported prostheses. A narrative review.